2007
DOI: 10.1007/s10532-006-9089-z
|View full text |Cite
|
Sign up to set email alerts
|

Polyester-degrading thermophilic actinomycetes isolated from different environment in Taiwan

Abstract: Thermophilic actinomycetes strains were isolated from various environment in Taiwan and screened for degradation of poly(ethylene succinate) (PES), poly(epsilon-caprolactone) (PCL) and/or poly(beta-hydroxybutyrate) (PHB) by the clear-zone method. Out of 341 strains of thermophilic actinomycetes, 105 isolates were PHB-degraders (30.8%), 198 isolates were PCL-decomposers (58.1%), and 99 isolates could degrade PES (29.0%). Furthermore, 77 isolates could degrade both PHB and PCL (22.6%), 35 isolates could degrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…It belongs to the class b-proteobacteria. The degradation of PCL has been studied by various researchers (Hirotsu et al, 2000;Khatiwala et al, 2008;Li et al, 2012) as well as under thermophilic conditions (Sanchez et al, 2000;Nakasaki et al, 2006;Tseng et al, 2007;Chua et al, 2013). However, there are limited reports on degradation of polyesters by thermophilic strain from genus Ralstonia as well as the depolymerases from Ralstonia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It belongs to the class b-proteobacteria. The degradation of PCL has been studied by various researchers (Hirotsu et al, 2000;Khatiwala et al, 2008;Li et al, 2012) as well as under thermophilic conditions (Sanchez et al, 2000;Nakasaki et al, 2006;Tseng et al, 2007;Chua et al, 2013). However, there are limited reports on degradation of polyesters by thermophilic strain from genus Ralstonia as well as the depolymerases from Ralstonia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Polymer biodegradability depends on molecular weight, crystallinity and physical forms (Gu et al, 2000). Hoang et al (2007) and Tseng et al (2007) reported thermophilic actinomycetes that could degrade PCL. Some of the bacterial and fungal strains such as Alcaligenes faecalis and Paecilomyces lilacinus, respectively, were demonstrated to degrade PCL (Oda et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…was able to degrade 90% of PHB film after five days cultivation at 50°C [81] Furthermore, several thermophilic polyester degrading actinomycetes were isolated from different ecosystems. Out of 341 strains, 31 isolates were PHB, PCL and PES degraders and these isolates were identified as members of the genus Actinomadura, Microbispora, Streptomyces, Thermoactinomyces and Saccharomonospora [82]. The miscibility, morphology and biodegradability of PHB blends with PCL, polybutylene adipate (PBA), and poly(vinyl acetate) (PVAc) were investigated.…”
Section: Comparison Of the Biodegradation Of Pha With Other Biopolymersmentioning
confidence: 99%
“…Tseng et al (2007) reported thermophilic actinomycetes from Taiwan with 29.0% polyethylene succinate degradation efficiency. Tseng et al (2007) reported 31 isolates belonging to the genus Saccharomonospora, Streptomyces, Microbispora, Thermoactinomyces and Actinomadura for polymer degradation. Biodegradation of plastic employs different ways, and thermophilic composting serves as a promising method for removal of degradable plastic from the natural environment.…”
Section: Polyethylene Succinatementioning
confidence: 99%